Spatial Flood Risk Management Implementing Catchment-based Retention and Resilience on Private Land - Hartmann, Thomas; Slavíková, Lenka; Wilkinson, Mark E. (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Centralising the role of land and landowners, Spatial Flood Risk Management brings together knowledge from socio-economy, public policy, hydrology, geomorphology, and engineering to establish an interdisciplinary knowledge base on spatial approaches to managing flood risks.